Investigating the dependence of the hypoxia-inducible factor hydroxylases (factor inhibiting HIF and prolyl hydroxylase domain 2) on ascorbate and other reducing agents. - Flashman, E; Davies, S; Yeoh, K; Schofield, C (2010)
The HIF (hypoxia-inducible factor) hydroxylases [PHDs or EGLNs (prolyl hydroxylases), which in humans are PHD isoforms 1-3, and FIH (factor inhibiting HIF)] regulate HIF levels and activity. These enzymes are Fe(II)/2-oxoglutarate-dependent oxygenases, many of which are stimulated by ascorbate. We have investigated the ascorbate dependence of PHD2-catalysed hydroxylation of two prolyl hydroxylation sites in human HIF-1alpha, and of FIH-catalysed hydroxylation of asparaginyl hydroxylation sites in HIF-1alpha and in a consensus ankyrin repeat domain peptide. The initial rate and extent of hydroxylation was increased in the presence of ascorbate for each of these reactions. When ascorbate was replaced with structural analogues, the results revealed that the ascorbate side chain was not important in its contribution to HIF hydroxylase catalysis, whereas modifications to the ene-diol portion of the molecule negated the ability to promote hydroxylation. We investigated whether alternative reducing agents (glutathione and dithiothreitol) could be used to promote HIF hydroxylase activity, and found partial stimulation of hydroxylation in an apparently enzyme- and substrate-specific manner. The results raise the possibility of developing reducing agents targeted to specific HIF hydroxylase-catalysed reactions.